Sedative and antinociceptive effects of different detomidine constant rate infusions, with or without methadone in standing horses - Gozalo-Marcilla, M. [UNESP]; de Oliveira, A. R. [UNESP]; Fonseca, M. W. [UNESP]; Possebon, F. S. [UNESP]; Pelligand, L.; Taylor, P. M.; Luna, S. P.L. [UNESP] (Wiley, 2019)
Background: Standing surgery avoids the risks of general anaesthesia in horses. Objectives: To assess sedation, antinociception and gastrointestinal motility in standing horses after a detomidine loading dose and 2-h constant rate intravenous (i.v.) infusion, with or without methadone. Study design: Blinded, randomised, crossover with seven healthy adult cross-bred horses, three geldings and four females (404 ± 22 kg). Methods: Five i.v. treatments were administered to all horses with 1-week washout period: saline (SAL), detomidine low (2.5 μg/kg bwt + 6.25 μg/kg bwt/h) (DL) and high doses (5 μg/kg bwt + 12.5 μg/kg bwt/h) (DH) alone or combined with methadone (0.2 mg/kg bwt + 0.05 mg/kg bwt/h), (DLM) and (DHM), respectively. Height of head above the ground (HHAG), electrical (ET), thermal (TT) and mechanical (MT) nociceptive thresholds and gastrointestinal motility were evaluated at predetermined times between 5 and 240 min. A mixed effect model and Kruskal–Wallis test were used to analyse normally and non-normally distributed data, respectively. Results: Sedation (<50% basal HHAG) was achieved for the duration of the infusion, and for an additional 15 min in DH and DHM groups. Nociceptive thresholds were higher than baseline, to the greatest degree and the longest duration, with DHM (ET and TT for 135 min and MT for 150 min). After DH, TT was significantly higher than baseline from 30 to 120 min and MT from 15 to 135 min. After DLM, ET was increased at 90 min, TT at 30 min and MT for 120 min. Gastrointestinal motility was reduced for up to 135 min after DL, 150 min after DLM and 210 min after DH and DHM. Main limitations: Nociceptive thresholds are not equivalent to surgical stimuli. Conclusion: Methadone with the highest detomidine dose (DHM) may provide sufficient sedation and analgesia for standing surgical procedures and warrants further investigation.
Keywords: electrical stimulus; equine; mechanical stimulus; opioids; thermal stimulus; α2-agonists